(untitled) (Brazilian Journal of Health Research, 2019)
Introduction: The culture of a given society is found in the beliefs, norms, vocabulary, customs and values of its population. Objective: Identifying scientific evidence about cultural features affecting the health of Brazilian families. Methods: Integrative literature review comprising full studies conducted with primary data, published from 2009 to 2019 in the electronic database “Latin American and Caribbean Health Sciences Literature”. These studies were written in English, Spanish and Portuguese, and they presented the following terms: Nursing, Family and Culture. Fourteen studies met the inclusion criteria. After full reading, they had their information synthesized, grouped based on similarities to the topic and subjected to descriptive analysis. Results: Studies were synthetized into the following categories: “Arts in everyday life”, “Organization of families” and “Human relations in health care”. Conclusion: The influence of arts stood out among the cultural features affecting the health of families due to song lyrics that normalized the gender violence culture. With respect to the organization of families, their exposure to patriarchal culture, to prejudice against homoparenting and to the economic vulnerability of single-parent families was evident. Category human relations has evidenced fragility in the health care provided to children, adolescents, women, indigenous people, individuals with special needs and rural workers.